SERVICE QUALITY ANALYSIS IN CV. KEMALA AMAN FINANCE (KAF) BENGKULU CITY - Desi Ratnasari; Sulisti Afriani; Siti Hanila (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
This study aims to analyze the quality of service on CV. Kemala Aman Finance (KAF) of Bengkulu city which is analyzed using Importance-Performance Analysis (IPA) method. The company focuses on a private institution engaged in micro Finance credit services engaged in the offering of capital services that has been established in 2011 until now. Based on the characteristics of the study obtained research samples as many as 112 respondents using the total sampling method. This type of research is descriptive research with quantitative approach by disseminating questionnaires. The results of the study obtained the quality of services provided by CV. Kemala Aman Finance (KAF) Bengkulu city of 5 dimensions falls into the category of quite satisfactory. With the score obtained by all dimensions are Tangible (85.07), Reliability (84.24), Responsiveness (83.41), Assurance (82.78), Empathy (83.20) with the highest score of 85.07 on tangible.